2018
DOI: 10.1515/humo-2017-0029
|View full text |Cite
|
Sign up to set email alerts
|

Influence of nutrition and genetics on performance: a pilot study in a group of gymnasts

Abstract: Purpose. Energy requirements in sports performance are affected by numerous factors: physical characteristics, age, genetic basis, sports discipline. The Food and Nutrition board recommended nutrition based on age, height, and body weight gain in relation to physical activity. some genetic factors, such as the PPAr-encoding gene, play a key role in metabolism. The aim of the study was to investigate the effect of specific snacks on performance. Methods. seventeen girls aged 10-14 years practising artistic gymn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Consequently, they are fundamental to guarantee a good physical performance. the adequate protein intake indicated by the American College of Sports Medicine (ACSM) is 1.2-1.8 g/kg of body mass for active adults [68,69], with athletes requiring higher protein intake to maintain protein synthesis [70]. In particular, a recent study has shown that the ingestion of 20 g of protein post-exercise helps maintain positive protein balance following exercise [71].…”
Section: Proteinmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, they are fundamental to guarantee a good physical performance. the adequate protein intake indicated by the American College of Sports Medicine (ACSM) is 1.2-1.8 g/kg of body mass for active adults [68,69], with athletes requiring higher protein intake to maintain protein synthesis [70]. In particular, a recent study has shown that the ingestion of 20 g of protein post-exercise helps maintain positive protein balance following exercise [71].…”
Section: Proteinmentioning
confidence: 99%
“…However, burke et al [72] suggested that carbohydrate ingestion during activities lasting 45 minutes or longer provides an ergogenic effect with doses varying from small ones up to 90 g/ hour, whereas ACSM recommends that athletes should ingest simple sugars at the rate of 30-60 g/hour for exercise lasting longer than 60 minutes. Additionally, Amato et al [69] showed that gymnastics performance improved after eating a carbohydrate snack compared with a different pre-exercise meal.…”
Section: Carbohydratementioning
confidence: 99%
“…Bone mineral density is modified by various factors and in particular by diet, by nutritional status and exercise (1,2,3). Athletes have a higher bone turnover compared to sedentary individuals.…”
Section: Introductionmentioning
confidence: 99%
“…An important distinction must be made between endurance training and resistance training. In fact, some studies show that the post workout supplementation with isolated proteins does not improve endurance or aerobic/anaerobic performance more than carbs supplementation (Alessandra Amato et al, 2017;D'Lugos et al, 2016). But at the same time, it can be useful to reduce muscle damage markers such as creatine kinase and muscle pain 12-24 hours after exercise (Breen, Tipton, & Jeukendrup, 2010;Romano-Ely, Todd, Saunders, & Laurent, 2006;Saunders, Luden, & Herrick, 2007;Valentine, Saunders, Todd, & St Laurent, 2008).…”
Section: Introductionmentioning
confidence: 99%